2014
DOI: 10.1186/1750-1172-9-32
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease in patients with Morquio A syndrome: results from an international patient-reported outcomes survey

Abstract: BackgroundMorquio A syndrome (or mucopolysaccharidosis IVa) is an ultra-rare multi-organ disease, resulting in significantly impaired functional capacity, mobility and quality of life (QoL).MethodsThis patient-reported outcomes survey evaluated the global burden of Morquio A among adults (≥18 years, N = 27) and children (7-17 years, N = 36), including the impact on mobility, QoL, pain and fatigue. QoL was assessed using the general Health-Related Quality of Life (HRQoL) questionnaire (the EuroQol [EQ]-5D-5L). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(149 citation statements)
references
References 11 publications
6
137
0
6
Order By: Relevance
“…The APPT showed a pain burden at baseline, predominantly in the lower extremities, which confirms the findings from a patient‐reported outcomes study in Morquio A patients in which 64% of 36 children and 74% of 27 adults reported joint pain, most often in the lower extremities [Hendriksz et al, 2014b]. Pain was also considerably reduced from baseline by ERT in this pilot study.…”
Section: Discussionsupporting
confidence: 88%
“…The APPT showed a pain burden at baseline, predominantly in the lower extremities, which confirms the findings from a patient‐reported outcomes study in Morquio A patients in which 64% of 36 children and 74% of 27 adults reported joint pain, most often in the lower extremities [Hendriksz et al, 2014b]. Pain was also considerably reduced from baseline by ERT in this pilot study.…”
Section: Discussionsupporting
confidence: 88%
“…Available data include two studies. Hendriksz et al (2014) examined overall quality of life (QOL) in children and adults with Morquio A, using the HealthRelated Quality of Life (HRQoL) EuroQoL (EQ)-5D-5L questionnaire. Overall QOL was inversely related to patient mobility, such that high reliance on a wheelchair for mobility significantly reduced QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien hay diferencias en la presentación clínica, se han descrito radiológicamente los siguientes hallazgos: silla turca en forma de J, aumento del espacio diploico en la calota, clavículas cortas y gruesas, cuerpo vertebral en pico y borde posterior festoneado (Figura 1), alas ilíacas redondeadas, coxa valga (Figura 2), epífisis hipoplásicas (predominantemente, a nivel distal de cúbito y radio) (Figura 3), engrosamiento y acortamiento diafisario, retraso de la edad ósea con respecto a la edad cronológica en los huesos de la mano (disociación carpo-epifisaria) y osificación tardía o no presente del escafoides (Figura 4). [1][2][3] El análisis de la frecuencia de los distintos componentes de la DM sobre la base del registro Morquio muestra en orden decreciente genu valgo, giba lumbar (Figura 1), pectumcarinatum, deformidades en las muñecas, la cadera, el fémur y el tobillo. 7 Posiblemente, otra manifestación característica y que solo se evidencia en la MPS IV-A es la hiperlaxitud articular (Figura 4).…”
Section: Manifestaciones Clínicasunclassified
“…InTRODuCCIÓn La mucopolisacaridosis tipo IV-A (MPS IV-A), también conocida como enfermedad de Morquio, es una enfermedad por depósito lisosomal con herencia autosómica recesiva. 1 F u e d e s c r i t a e n 1 9 2 9 e n f o r m a separada por Luis Morquio (pediatra de Uruguay) y James Brailsford ( r a d i ó l o g o d e I n g l a t e r r a ) . S u incidencia en la población general es de 1/200 000, aunque se han reportado desde 1/76 000 nacidos vivos en el norte de Irlanda hasta 1/640 000 en el oeste de Australia.…”
Section: Introductionunclassified
See 1 more Smart Citation